Dietary Intake, Body Composition, and Nutrition Knowledge of Irish Dancers. Issue 3 (September 2020) - Challis, Jasmine; Cahalan, Roisin; Jakeman, Phil; NiBhriain, Orfhlaith; Cronin, Linda; Reeves, Sue
Irish dance requires lengthy, intensive training to perform at a high level in competitions and professionally. Irish dancers have been known to have high injury rates. Appropriate nutrient and fluid intakes have been shown to minimize the risk of fatigue and injury during training and performance in sport, but there is a lack of evidence as to whether and how this might apply in Irish dance. Forty adult Irish dancers, 35 females (age 21 ± 3 years) and five males (aged 27 ± 8 years), professionals or in full time training, were recruited for this study to investigate nutrition knowledge, dietary intake, and body composition. Participants were asked to complete "The Sport Nutrition Questionnaire, " a sport- and dance-specific nutrition knowledge questionnaire, 4 day estimated food diaries, and undertake a dual x-ray absorptiometry (DXA) scan to assess body composition. Food diaries were analyzed using Dietplan 7. Reported energy, fiber, iron (females), magnesium (females), selenium, iodine (females), and folate (females) intakes were below United Kingdom dietary reference values. Fruit and vegetable intakes were low: 2.7 ± 1.4 portions per day. Sixteen percent of days reported contained no fruits or vegetables. Mean body mass index (BMI) for 35 female participants was 23.2 ±3.3 kg/m 2, mean BMI for five male participants was 22.2 ±1.6 kg/m 2 . Mean body fat measured by DXA in 18 female participants was 33.4% ± 6.9%, which was higher than seen in other dance populations. Mean lean mass was 40.8 ± 5.6 kg. Mean score for the nutrition knowledge questionnaire in which the maximum score is 65, was 30.5 ± 7.6 (47% ± 11.7%), range: 9 to 44 (14% to 68%). The ability of the Irish dancers to correctly identify foods as being high or low in carbohydrate, protein, and fat varied widely. Body composition did not correlate with intake of any nutrient but did correlate with nutrition knowledge questionnaire score (r = -.663, p < 0.001). Given the dietary intakes and nutrition knowledge exhibited by the dancers in this study, further work is needed to inform and improve diets and support the demands of Irish dance.